Germination of Amburana cearensis (Allemao) A. C. Sm. submitted to different substrates (Research, Society and Development, 2020)
Caatinga forest species are commonly used for the recovery of degraded areas, normally for the production of seedlings the seeds are placed to germinate on substrates. With that, the objective of this research was to evaluate different types of substrates for the germination of A. cearensis seeds, seeking to determine the most suitable to promote the initial development of the species. The experiment was carried out in a completely randomized design, with five substrates, being sand, fine texture vermiculite, thick texture vermiculite, humus and coconut fiber, with four replications of 25 seeds. After sowing, irrigation was performed daily until the 30th day after sowing. The percentage of emergence, mean time of emergence, emergency speed index, height of seedlings, root length, dry mass of the aerial part and root system and the total dry mass of seedlings were evaluated. The medium texture vermiculite substrate provided the best results regarding the percentage of emergence, the emergence speed index, the length of the aerial part and the root system. The medium texture vermiculite is the most suitable substrate for the initial development of A. cearensis.